SNAP participants' purchasing patterns at a food co-op during the COVID-19 pandemic - Molly Parker; Valisa Hedrick; Sam Hedges; Elizabeth Borst; Meredith Ledlie Johnson; Maureen Best; Sarah Misyak (Journal of Agriculture, Food Systems, and Community Development, 2021)
The COVID-19 pandemic has affected the food system, increasing barriers to food access and exacerbating food insecurity across the U.S. The Virginia state government initiated a stay-at-home order to help reduce the spread of COVID-19. Prior to the pandemic, the Virginia Fresh Match (VFM) Nutrition Incentive Network partnered with food retail outlets to provide Supplemental Nutrition Assistance Program (SNAP) participants point-of-purchase incentives (e.g., Double Up Food Bucks, SNAP Match), which function as matching discounts on fresh fruits and vegetables (F/V). These can enable participants to increase their purchasing power and potentially reduce food insecurity. In response to COVID-19, VFM removed the limit on incentive discounts (previously $10[1]) to further incentivize the purchase of fresh F/V by SNAP participants. This study sought to characterize the purchasing patterns of SNAP participants at a food co-operative (co-op) partnered with VFM before and during the Virginia stay-at-home order. A total of 654 transactions at the co-op were included. Independent t-tests were utilized to determine differences before and during the order. The results indicated a significant increase in the mean incentive discount received during the order (pre-shutdown=$3.95, inter-shutdown=$5.01, p=0.035); however, simultaneously there was a decrease in the mean number of fresh F/V purchased (pre-shutdown=3.08, inter-shutdown=2.39, p=0.015). Although F/V purchases decreased, the presence of unlimited point-of-purchase incentives at the food co-op may have helped prevent a greater decline in fresh F/V purchases and helped increase access to fresh F/V in this population during the onset of the COVID-19 pandemic.